Alice Walkers “ The Color Purple “ – A paradigm of Quest for Self - Kumar, Dr Somanchi Sai (The journal of contemporary issues in business and government, 2019)
Afro-american women are discriminated from their own community men and the White men and White women. These women have been considered to the least beings in the world. Even the basic rights are regretted for them. They have been marginalized in the society and are treated as slaves and low paid labourers. Black women have been undergoing class, race, social oppression and found voiceless against the odds of the society. This paper aims at bringing out the trials and troubles faced by women characters in the novel The Color Purple by Alice Walker. Women urge to own a self identity. This search for self is not an easy task especially when it comes to a Black Women. It axiomatically becomes a great matter of struggle. The character Celie is shown to be submissive and mild and had the fear of men. It is through education and economic independence that a woman is able to gather strength and courage and live independently in the society. The Color Purple has the theme of sexist oppression, patriarchal supremacy and oppression of Black women, class struggles and status of Afro-American women.